Kluver-Bucy Syndrome in a Patient with Bipolar Affective Disorder: A Case Report - Bahnet, Madhur; Paudel, Luna; Gajurel, Bikram Prasad; Sapkota, Nidesh; Rauniyar, Raj Kumar (Journal of Lumbini Medical College, 2018)
Introduction: Kluver and Bucy described a behavioral syndrome in rhesus monkeys following bilateral temporal lobectomy which included psychic blindness, hyperorality, hypermetamorphosis, hypersexuality, and emotional unresponsiveness. Case report: A 44 years old right handed male of Indo-aryan origin, blacksmith by profession, had presented in manic phase of bipolar illness. He had hypersexuality, hypermetamorphosis, hyperorality, and altered dietary habits along with amnesia and fleeting misrecognition of even his close relatives. MRI of the patient showed mild cerebral atrophy with right temporal lobe atrophy. The patient was treated with lithium and olanzapine along with benzodiazepines. The symptoms resolved gradually with resolution of the manic phase. Patient had similar features in the previous manic episode as well that resolved with resolution of mania. Conclusion: The symptoms of Kluver-Bucy syndrome like increased libido, increased activity might be confused with that of mania. Other features of Kluver-Bucy syndrome and the overt hypersexuality could help identify it even during manic phase of bipolar illness. DOI: https://doi.org/10.22502/jlmc.v6i1.183